Systemic lupus erythematosus: novel aspects of pathogenesis and treatment 2 - Putterman, Chaim; Schwartz, Noa (Henry Stewart Talks, 2019)
Therapeutic strategies, B cell targeting agents, T cell/Co-stimulation inhibition, Innate immunity targets, Toleragenic agents, Small molecule and complement inhibition, Future directions